Personal Dan Sosial Yang Mempengaruhi Sikap Remaja Terhadap Hubungan Seks Pranikah - Setya Asih Widyastuti, Elisabet (Jurnal Promosi Kesehatan Indonesia, 2009)
Background: Adolescents are important groups that reported have potentially high risk from unwanted pregnancy, STIs and HIV/AIDS infections. Recent studies reported that they were earlier engaged premarital sex, have multiple partners and inconsistent on using condom.Adolescents who are living in brothel areas, their daily lives were exposed by prostitutions environment and living in more permissive sub-culture.Method: This current study that conducted at two brothels in Semarang namely Sunan Kuning and Gambilangu in 2008 is to examine and to understand the personal and social factors influencing adolescents’ attitudes toward premarital sex. A cross sectional study with both quantitative and qualitative approaches was sequence applied. Cumulatively, 67 adolescents (15-19 years) were interviewed; 5 participants and 8 informants were in-depth interviewed trough this study. Chi square and logistic regression test applied to examine the relationship between independent variables and dependent variable. Furthermore, content analyses technique was applied to analyze case study.Result: The research findings reported that brothels were not conducive place for adolescents to growing up, they were reported obtain negative impacts from their environment such as stigmatized, school dropped out, alcohol consuming, and exposed by sexual activities: observe people kissing, hugging, erotic dancing, and having sex. Those sexual exposures could lead adolescents into some risky behaviour. The adolescents’ acceptance of premarital intercourse was range between 7.5 – 37.3 percent at any relationship levels; this result was higher compared with other populations of non brothels adolescents. The acceptance level of premarital sex increased when it was done in more serious relationship. Bivariate analyses suggested that sex, close friends’ sexual attitudes and sexual exposure were statistically significant have correlation with adolescents attitudes toward premarital sex. In addition, multivariate analyses revealed that close friends’ sexual attitudes was the most influencing the occurrence of adolescents’ attitudes toward premarital sex, next followed by sex. It means adolescents who have liberal close friends tend to have risk 32,5 times to be more permissive toward premarital sex than those have traditional one; male have risk 4.9 times to be more permissive toward premarital sex than female.Key words: adolescents, sexuality, premarital, sex, permissiveness